Utilization of Waste Cooking Oil as Biodiesel for Portable Stoves: Comparison of Homogeneous and Heterogeneous Catalysts - Sipayung, Rosmawati; Amalia, Rahma; Ra'ida Raudhatussya'rifah; Rara Ayu Lestary; Widyastuti, Nita; Mundarti, Sri; Nazarudin (Kampus Akademik Publiser, 2025)
This research investigates the performance comparison between homogeneous (NaOH) and heterogeneous (CaO) catalyst in biodiesel production from waste cooking oil, specifically focusing on their application as fuel for portable stoves. The study examines the effects of catalyst type with NaOH concentrations of 1%, 2%, and 3%, and CaO concentrations of 4% and 6%, along with methanol-to-oil molar ratios (1:6 and 1:12) on biodiesel yield, product color, and flame characteristics. Results show that NaOH catalyst achieved higher yields (92.30%) at 3% concentration with a 1:6 methanol-to-oil ratio, while CaO catalyst reached maximum yields of 42.00% at 6% concentration with a 1:12 ratio. NaOH-catalyzed biodiesel consistently produced clear yellow coloration, whereas CaO-catalyzed biodiesel showed varying clarity depending on process conditions. In portable stove applications, NaOH-catalyzed biodiesel demonstrated superior performance with faster combustion rates (0.0607 ml/second) and blue flames, compared to CaO-catalyzed biodiesel's slower combustion (0.0412 ml/second) and yellowish-red flames.